Developing G-T-B glass system doped holmium oxide for radiation absorption and optical applications - M.I. Sayyed; M.H.A. Mhareb; Kawa M. Kaky; K.A. Mahmoud; Abed Jawad Kadhim; Yasser Maghrbi (Journal of Science: Advanced Materials and Devices)
The current work developed and fabricated three groups of the Ho2O3-doped G-T-B (germanate-telluride-borate) glass system via melt-quenching followed by an annealing process with a chemical formula of [33.75B2O3-20TeO2-10GeO2-35MgO-1.25Ho2O3], [32.5B2O3-20TeO2-10GeO2-35MgO-2.5Ho2O3], and [31.25B2O3-20TeO2-10GeO2-35MgO-3.75 Ho2O3]. The synthesized glasses are clear, yellow, transparent, homogeneous, and bubble-free. The glassy nature has been examined by utilizing X-ray diffraction. Optical absorption for Ho1.25, Ho2.5, and Ho3.75 has been recorded; based on these records, the Mott and Davis relation was used to determine the energy band gap. An Archimedes' theory-based sensitive density balance was used to find the densities (ρ) of all the materials studied. The mechanical characteristics were theoretically determined using the Makishima–Mackenzie model. Monte Carlo simulation over the 0.015–2.506 MeV energy range was employed to investigate the fabricated glass samples' γ-ray shielding features. The study found that increased Ho2O3 across the concentration of 1.25–3.75 mol% increased the fabricated glasses' linear attenuation coefficient (LAC) by 19.56 % at 0.015 MeV, 20.22 % at 0.122 MeV, 5.31 % at 0.662 MeV, and 4.42 % at 2.506 MeV. A slight radiation protection efficiency increase followed this LAC enhancement, while the half-value thickness, thickness equivalent lead, and transmission factor were reduced when the Ho2O3 content grew within the fabricated glasses.